Ichneumonidae (Hymenoptera) as parasitoid of Diptera Muscomorpha in Brazil - Carlos Henrique Marchiori (Open Journal of Biological Sciences - Peertechz Publications, 2020)
The flies included in the infra-order Muscomorpha have medical and veterinary importance, since they may produce myiasis and act in carrying pathogens to man and animals. They have been found to carry more than 100 species of disease-causing organisms such as bacteria, protozoa and helminths. Parasitoids are responsible for reducing the populations of flies that proliferate on various substrates. Evaluation of these species for natural control over these insects is important for enabling studies that aim towards subsequent selection of species for use in biological control programs. The objective of this study was to verify Family Ichneumonidae specimens as Diptera Muschomorpha parasitoid in Brazil. To obtain the parasitoids, the contents of the traps were placed in plastic containers with a layer of sand for use as a substrate for transformation of the larvae into pupae. This sand was sifted after being in the fields for 15days and the pupae were extracted from it and were individually placed in gelatin capsules (number 00) in order to obtain the flies and/or parasitoids. From November 2003 to January 2004, 50 Hemilucilia segmentaria (Fabricius, 1805) pupae were collected, from which 10 emerged morphological species of Pimpla sp. (Hymenoptera: Ichneumonidae) percentage of parasitism was 20.0%. This paper describes the first case of Pimple sp. as H, segmentaria parasitoid in the world.